2022
DOI: 10.3390/ijms23105589
|View full text |Cite
|
Sign up to set email alerts
|

PAX9 in Cancer Development

Abstract: Paired box 9 (PAX9) is a transcription factor of the PAX family functioning as both a transcriptional activator and repressor. Its functional roles in the embryonic development of various tissues and organs have been well studied. However, its roles and molecular mechanisms in cancer development are largely unknown. Here, we review the current understanding of PAX9 expression, upstream regulation of PAX9, and PAX9 downstream events in cancer development. Promoter hypermethylation, promoter SNP, microRNA, and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 75 publications
1
6
0
Order By: Relevance
“…We focused on the transcription factor PAX9 on the basis of results from CAGE and GSEA technologies. PAX9 belongs to the paired box family that encodes a group of growth-and development-regulation-related transcription factors [39]. GSEA results also indicated the involvement of PAX9 in head morphogenesis, body morphogenesis, face development, tissue development, and regulation of animal organ morphogenesis.…”
Section: Discussionmentioning
confidence: 91%
“…We focused on the transcription factor PAX9 on the basis of results from CAGE and GSEA technologies. PAX9 belongs to the paired box family that encodes a group of growth-and development-regulation-related transcription factors [39]. GSEA results also indicated the involvement of PAX9 in head morphogenesis, body morphogenesis, face development, tissue development, and regulation of animal organ morphogenesis.…”
Section: Discussionmentioning
confidence: 91%
“…For example, recent studies have shown that PAX8 can regulate tumor-stroma interaction, cell adhesion, proliferation, and migration, and mutations in PAX8 are thought to be associated with the development and progression of 90% of ovarian cancers [28,29]. PAX9 gene mutation, ampli cation and deletion can promote the development of lung adenocarcinoma, squamous cell carcinoma, cervical cancer, ovarian cancer and breast cancer [30]. PAX8 is highly expressed in cervical cancer, and PAX8 transcripts are upregulated in cervical cancer samples, suggesting a correlation with cervical cancer development [31], and PAX8 expression is also upregulated in uterine adenocarcinoma, squamous cell carcinoma, endometrioid adenocarcinoma, and adenosquamous carcinoma [32][33][34][35][36][37][38][39][40][41][42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…We focused on the transcription factor PAX9 based on results from CAGE and GSEA technologies. PAX9 belongs to the paired box family that encodes a group of growth- and development-regulation-related transcription factors [ 49 ]. GSEA results also indicated the involvement of PAX9 in head morphogenesis, body morphogenesis, face development, tissue development, and regulation of animal organ morphogenesis.…”
Section: Discussionmentioning
confidence: 99%